Development of D-α-Tocopherol polyethylene glycol 1000 succinate fabricated nanostructural lipid carrier of sorafenib tosylate for metastatic colorectal targeting application: Stability, physical characterization, cytotoxicity, and apoptotic studies against SW48 cells PTEN - Bhattacharya, Sankha; Sharma, Satyam; Prajapati, Bhupendra G. (Frontiers in Oncology, 2022)
The study aimed to create D-α-Tocopherol polyethylene glycol 1000 succinate (TPGS) nanostructured lipid carriers (NLC) of sorafenib tosylate (ST) as lymphatic delivery systems (LDDS) to fight Metastatic colorectal cancer. Initially, ST-SLN, ST-NLC, and ST-LNE were formulated considering oleic acid (OA), glycerol monolinoleate (GMO), glycerol monolinoleate (GML) as solid lipid and further characterised, and tested for stability. The most stable ST-NLC was fabricated with TPGS to produce ST-TPGS-NLC and evaluated by performing in vitro drug profiling, in vitro cytotoxicity, and apoptotic studies against human female colorectal adenocarcinoma cell lines (SW48 Cells PTEN). Stability studies on three lipidic nanoparticles (ST-SLN, ST-NLC, ST-LEN) showed particle size, polydispersity index, and zeta potential ranging from 165 nm to 298 nm, 0.125 to 0.288, and -31 mV to -16 mV. At 1600 minutes, more than 80% of ST-NLC1 was released, confirming the sustained release pattern of the formulation. ST-NLC and ST-TPGS-NLC have entrapment efficiencies above 50%. Pure ST’s IC50 at 72 hr was 3.45 µg/mL, while 1.56 µg/mL was for ST-TPGS-NLC. The ST-TPGS-NLC reduced the number of livings SW48 Cells PTEN from 91% to 5%, compared to 75% to 8% of pure ST. The ST-TPGS-NLC is a promising LDDS for delivering ST for metastatic colorectal cancer.